Horizontal Single Axis Solar Tracker Using Arduino Approach - Siti Amely Jumaat; Adam Afiq Azlan Tan; Mohd Noor Abdullah; Nur Hanis Radzi; Rohaiza Hamdan; Suriana Salimin; Muhammad Nafis bin Ismail (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This project discusses on the development of horizontal single axis solar tracker using Arduino UNO which is cheaper, less complex and can still achieved the required efficiency. For the development of horizontal single axis solar tracking system, five light dependent resistors (LDR) has been used for sunlight detection and to capture the maximum light intensity. A servo motor is used to rotate the solar panel to the maximum light source sensing by the light dependent resistor (LDR) in order to increase the efficiency of the solar panel and generate the maximum energy. The efficiency of the system has been tested and compared with the static solar panel on several time intervals. A small prototype of horizontal single axis solar tracking system will be constructed to implement the design methodology presented here. As a result of solar tracking system, solar panel will generate more power, voltage, current value and higher efficiency.